(untitled) (Journal of the College of Education for Women, 2019)
This study aims to focus on the Motives behind volunteer work among a sample of volunteers working in civil society organizations and check if there are statistical differences with those variables according to (gender, age, job, period of volunteer work, and residence. The sample consists of (220 )volunteers,(189) male and(31) female from southern, northern and central governorate .The Volunteer Functions Inventory(VFI)(Clary & et al,1989)was applied, It consisting of(30) items with six fields( Values, Understanding, Social motives, Career, Protective, Enhancement). The results show that the most common and important motivations are (Values, Understanding, and social motivations), there are differences among Males and females in Protective motivation in favor of females and for the age variables, there are differences on career motivation in favor of the oldest, and there are no significant differences in the other variables such as(volunteer job, duration of volunteer work and place of residence).